Rising damp in historical buildings - M. I. TORRES (2003)
The investigation of moisture transfer in buildings' walls is extremely important for the characterisation of behaviour in connection with durability and degradation of appearance. Due to the complexity of the problem, it is frequently extremely difficult to give a scientific explanation of the many ways in which rising damp can occur. While conducting a study of rising damp, it is important to perform a two-dimensional analysis of the simultaneous heat and moisture transfer, due to the great thickness and the homogeneity of the masonry of historical constructions. There are several computational programs that allow this kind of analysis and we have explored them for different boundary conditions. In order to validate the numerical model, we are developing an experimental device. In this paper we intend to show the results of the simulations that we have made up until now and the experimental device that we are developing.